Corporate Social Responsibility in SMEs: The Role of Non-Audit Services - Yuvaraj, Ganesan; Hasnah, Haron; Azlan, Amran; Say, Keat Ooi (IGI Global, 2017)
Given The increasing imporTance of The role played by small and medium-sized enTerprises (SMEs) wiThin The developing economy, This paper inTends To provide furrher insighT inTO corporaTe social responsibiliTy (CSR) pracTices among SMEs. WiThin This conTexT, The purpose is TO propose The role of non-audiT services (NAS), which COJITrib uTe TO The possible explanaTion of The SME adopTion of CSR pracTices. A concepTual approach is wken whereby This paper is based on lll! exTensive liTermure review of NAS and CSR pracTices in The SM E conTexT. Then, based on The knowledge-based view ( KBV), This paper seT TO explain and highlighT The role of NAS play To enhance CSR pracTices among SMEs. This paper provides a TheoreTical discussion on The imporTance ofCSR in ensuring The survival of The SMEs. AlThough The proposiTion ofNAS is relaTively new, iT provides an inTeresTing and remarkable avenue for furTher research especially in The developing counTry. Overall, This p·aper draws auenrion TO The imporTance of NAS in enhancing The survival and performance of The SMEs.